Cyberstalking perpetration among young adults: an assessment of the effects of low self-control and moral disengagement - Fissel, Erica R. (Crime & delinquency, 2021)
The current study sought to explain cyberstalking perpetration using low self-control and moral disengagement frameworks. Self-report survey data collected from a Mechanical Turk sample of 1,500 young adults aged 18 to 25 years old revealed that approximately 22% of the sample had engaged in cyberstalking perpetration during their lifetime. Findings also generally supported the self-control and moral disengagement frameworks. Respondents with higher levels of low self-control were more likely to engage in cyberstalking perpetration, as were those respondents who had a higher moral disengagement score. The interaction between low self-control and moral disengagement, however, did not yield a significant effect.